2001
DOI: 10.1029/2000wr900357
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Canadian streamflow

Abstract: Abstract. This study presents trends computed for the past 30-50 years for 11 hydroclimatic variables obtained from the recently created Canadian Reference Hydrometric Basin Network database. It was found that annual mean streamflow has generally decreased during the periods, with significant decreases detected in the southern part of the country. Monthly mean streamflow for most months also decreased, with the greatest decreases occurring in August and September. The exceptions are March and April, when signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

31
465
4
21

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 654 publications
(521 citation statements)
references
References 21 publications
31
465
4
21
Order By: Relevance
“…These include work in the US (Lins and Slack, 1999;Douglas et al, 2000), Scandinavia (Lindstrom and Bergstrom, 2004), Canada (Zhang et al, 2001;Burn and Hag Elnur, 2002;Yue and Wang, 2002) and more recently, a global assessment by Svensson et al (2005). These studies present evidence of significant variability, but there are many inherent obstacles to attributing observed trends to climate change.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include work in the US (Lins and Slack, 1999;Douglas et al, 2000), Scandinavia (Lindstrom and Bergstrom, 2004), Canada (Zhang et al, 2001;Burn and Hag Elnur, 2002;Yue and Wang, 2002) and more recently, a global assessment by Svensson et al (2005). These studies present evidence of significant variability, but there are many inherent obstacles to attributing observed trends to climate change.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, trend studies in the US (Lins andSlack, 1999, Douglas et al, 2000) and Canada (Adamowski and Bocci, 2001;Zhang et al, 2001;Burn and Hag Elnur, 2002;Yue and Wang, 2002) have capitalised on networks of undisturbed, natural catchments, such as the representative hydrometric basin network (RHBN) of Canada. The scope for such an approach in much of Europe is limited and in the UK, the task of identifying and interpreting trends in river flow regimes is particularly challenging because of the high degree of heterogeneity in catchment geology, land use and climate -and the pervasive impact of anthropogenic disturbances on flow regimes.…”
Section: Introductionmentioning
confidence: 99%
“…Regional streamflow trend analyses will provide useful information for both policy makers and practitioners to undertake effective water resources planning and management at a regional scale. The studies addressing this topic include Lettenmaier et al (1994), Douglas et al (2000), Zhang et al (2001), Burn and Hag Elnur (2001), and others.…”
Section: Introductionmentioning
confidence: 99%
“…Lins and Slack (1999) applied the nonparametric Mann-Kendall test to study temporal trends of streamflow at 395 gauging stations across the USA and suggested that streamflow increased in most regions, except for the northwest and the southeast Pacific. Zhang et al (2001) pointed out that streamflow decreased significantly in most months, especially in August and September from 1947-1996 in southern Canada. Xu et al (2010) analyzed the trends of major hydroclimatic variables from in the Tarim River Basin of China and concluded that the impacts of increasing air temperature on streamflow showed different characteristics, depending on location and seasons.…”
Section: S L Sun Et Al: Past and Future Changes Of Streamflow In Pmentioning
confidence: 99%
“…In addition, climate change may even be speeded up in the future, consequently leading to an increase in probabilities of floods and droughts. Therefore, changes in water resources and the underlying driving forces due to climate changes have become research focuses (Andréasson et al, 2004;Christensen and Lettenmaier, 2007;Frederick and Major, 1997;Gül et al, 2010;Lins and Slack, 1999;Liu and Cui, 2009;Null et al, 2010;Piao et al, 2007;Thodsen, 2007;Vörösmarty et al, 2000;Xu et al, 2010;Zhang et al, 2001). Andréasson et al (2004) discussed the impacts of climate change on streamflow under three anthropogenic CO 2 emission scenarios with a hydrology model (HBV) and concluded that the influences of climate change based on hydrology cycle varied geographically.…”
Section: S L Sun Et Al: Past and Future Changes Of Streamflow In Pmentioning
confidence: 99%